Dirichlet Eigenvalue Ratios for the p-sub-Laplacian in the Carnot Group (Journal of Partial Differential Equations, 2009)
We prove some new Hardy type inequalities on the bounded domain with smooth boundary in the Carnot group. Several estimates of the first and second Dirichlet eigenvalues for the p-sub-Laplacian are established.